Impact of Electronic Customer Relationship Management on Customers Satisfaction of the Five Stars Hotels in Kuwait (Global Journal of Management and Business Research, 2018)
Abstract not found
Keywords: electronic customer relationship management; customers' satisfaction; the five stars hotels; kuwait